Natural course of spinal alignment and flexibility in middle-aged patients with nonoperatively treated adolescent idiopathic scoliosis - Sato, Masayuki; Makino, Tatsuo; Watanabe, Kei; Hasegawa, Kazuhiro; Ohashi, Masayuki; Hirano, Toru; Minato, Keitaro; Tashi, Hideki (Journal of Spine Research, 2024)
Introduction: Most studies to date of the natural course of adolescent idiopathic scoliosis (AIS) focused on the curve progression from skeletal maturity to adulthood, whereas few analyzed radiographic changes in coronal and sagittal alignments and curve flexibility during adulthood. This study aimed to reveal changes in scoliosis, curve flexibility, and sagittal alignment during middle age in patients with nonoperatively treated AIS.Subjects and Methods: This study included 27 female patients with nonoperatively treated AIS (magnitude >30° at skeletal maturity) who visited our hospital at least twice after 30 years of age at an interval of >1 year. Coronal and sagittal alignments were evaluated on standing whole-spine radiographs, while curve flexibility, L4/5 disc wedging, and lateral lumbar (L1-5) range of motion (ROM) were evaluated on supine spine-bending radiographs. Parameters were compared between the initial and final visits using the Wilcoxon rank-sum test. Differences were considered significant at p < 0.05.Results: The mean age was 40.7 (range, 30-58) years at the initial visit and 46.3 (range, 36-64) years at the final visit. The mean follow-up duration was 5.8 (range, 1.6-7.7) years. Curve magnitude did not change significantly during follow-up, changing from 24.0° to 24.0° for the upper thoracic curve (p = 0.78), from 54.0° to 55.0° for the main thoracic curve (p = 0.70), and from 44.0° to 50.0° for the TL/L curves (p = 0.95). UT and MT curve flexibility did not change significantly, while TL/L curve flexibility significantly decreased from 44.5% to 41.2% (p = 0.03). L4/5 disc wedging flexibility and lateral lumbar ROM did not change significantly (p > 0.3). Regarding sagittal alignment, lumbar lordosis decreased significantly from 51.0° to 39.0° (p < 0.001), while the sacral slope decreased significantly from 33.0° to 31.0° (p = 0.004). In contrast, the sagittal vertical axis increased significantly from −9.2 mm to −8.8 mm (p = 0.016), while pelvic tilt increased significantly from 13.0° to 17.0° (p<0.001). Conclusions: Here we demonstrated the 6-year natural course of nonoperatively treated AIS during middle age and found no significant changes in coronal curve magnitude but significant decreases in TL/L curve flexibility. Significant decreases in lumbar lordosis and pelvic retroversion were observed in the sagittal plane. These findings suggest that TL/L curve flexibility and sagittal alignment as well as coronal curve magnitude should be monitored during middle age.